The impact of non-significant variable decelerations appearing in the latent phase on delivery mode: a prospective cohort study - Salim Raed; Garmi Gali; Nachum Zohar; Shalev Eliezer (BMC, 2010)
Abstract Background Variable decelerations are the most frequent fetal heart rate changes that are related to labor. The objective of the study was to estimate the impact of non-significant variable decelerations (NSV) appearing during the latent phase of labor on delivery mode and neonatal outcome. Methods Women at term, who were in the latent phase of labor and had a singleton pregnancy, were prospectively included. Women were divided into three groups. All had a fetal heart rate tracing with normal baseline and variability. The study group was composed of women who had in addition NSV, Category II, according to the National Institute of Child Health and Human Development categorization system. Women who had Category I tracings composed the control group. Women who had non-repetitive severe variables (SV) composed a second control group (Category II-SV). Main outcome compared was mode of delivery. Secondary outcome was cord pH. One-way analysis of variance was used to compare the continuous demographic and clinical variables of the three groups. Backwards stepwise logistic regression using significant univariables was performed to determine which predicted operative delivery. P < 0.05 was considered significant. Results Of 1005 women who delivered during the study period 186 had Category II- NSV tracings (study group), 76 had Category II-SV and 251 had Category I tracings. Mode of delivery and indications for operative delivery were similar between women in Category II-NSV compared to Category I. In addition mean cord pH did not differ between the two groups. Conversely, women in Category II-SV, had a higher rate of cesarean or vacuum deliveries compared to the other groups (p = 0.0001). Beside, they had a significantly higher number of neonates born with cord pH between 7.0 to 7.1 (p = 0.03). Conclusions Non-significant variable decelerations in early stages of labor are probably a non-ominous sign for neonatal outcome and have no impact on delivery mode.